2012
DOI: 10.1111/j.1740-8261.2012.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Abdominal Computed Tomography and Abdominal Ultrasound in Sedated Dogs

Abstract: Abdominal ultrasound (US) is used frequently as a first-line screening tool for abdominal disease. Although computed tomography (CT) is superior to US in the diagnosis of some abdominal diseases, a major impediment is the requirement of general anesthesia to prevent motion and for safe restraint. With multidetector helical CT, faster examinations allow general anesthesia to be avoided, while producing diagnostic-quality images. Abdominal US and CT were compared for lesion detection in 27 sedated dogs, divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 12 publications
4
64
0
1
Order By: Relevance
“…The CT examination allows a precise diagnosis of many disorders and is comparable with or superior to other imaging modalities (Schwarz and Saunders ; Fields et al. ). The CT examination provides information about the location and morphological features of the prostate gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CT examination allows a precise diagnosis of many disorders and is comparable with or superior to other imaging modalities (Schwarz and Saunders ; Fields et al. ). The CT examination provides information about the location and morphological features of the prostate gland.…”
Section: Discussionmentioning
confidence: 99%
“…; Schwarz and Saunders ; Fields et al. ). There is limited data on the CT evaluation of the prostate gland in dogs (Dimitrov et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has also shown the migratory capacity of extruded gallbladder mucoceles in the abdomen as identified on abdominal ultrasound . Although mucoceles are readily detected using ultrasonography, relative to CT, it can result in longer scan times, greater patient discomfort from physical compression of the ultrasound probe, and incomplete evaluation of the abdomen in large patients . Thus, CT could allow faster and more complete abdominal evaluation for these patients, but scientific investigation of canine biliary contents in veterinary medicine using CT is minimal .…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) of the bowel has been described in the dog but is not always recommended for assessment of the colorectum because the presence of fecal material can limit accurate identification of lesions. Even when the bowel is empty, collapse of the gastrointestinal lumen and contraction of the muscular wall restricts assessment of wall thickness and lesion extent on both unenhanced and contrast‐enhanced CT. A noninvasive, low‐risk technique of CT imaging of the large bowel with luminal insufflation of gas (CT pneumocolonography) is used in people to improve visual assessment of lesions, and a technique for CT pneumocolonography has been described in a cohort of normal dogs …”
mentioning
confidence: 99%